Diversity of true bugs (Hemiptera: Heteroptera) of the Southern Aral Sea Region, Uzbekistan - M.ZH. MEDETOV; J.K. ABDULLAEVA; AKHMED REYMOV; A.M. MIRATDINOVA; A.K. SEYTMURATOV; J.D. TAJIBAEVA; R.S. KADIROV; N.A. UTEMURATOV; S.K. KIMYONAZAROV; JASUR KUDRATOV; R.S. URAZOVA; X.A. KELDIYOROVA; U.B. URALOV (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Medetov MZH, Abdullaeva JK, Reymov A, Miratdinova AM, Seytmuratov AK, Tajibaeva JD, Kadirov RS, Utemuratov NA, Kimyonazarov SK, Kudratov J, Urazova RS, Keldiyorova XX, Uralov UB. 2025. Diversity of true bugs (Hemiptera: Heteroptera) of the Southern Aral Sea Region, Uzbekistan. Biodiversitas 26: 3125-3135. This article presents the results of a scientific study conducted in 2021-2023 on screening representatives of the order Heteroptera in various regions of the Southern Aral Sea, Uzbekistan, using modern zoological and ecological methods and the literature review of the available scientific sources. It was noted that the hemipterans in the Southern Aral Sea Region consist of 258 species belonging to 4 infraorders, 13 superfamilies, 25 families, 35 subfamilies, 35 tribes, 104 genera and 3 subgenera. According to the distribution of hemipterans in the Southern Aral Sea Region in terms of infraorers, 132 species belong to the infraorder Pentatomomorpha (51.2%), 106 species to Cimicomorpha (41.1%), 13 species to Nepomorpha (5.03%), 7 species to Gerromorpha (2.7%) and the infraorder Gerro-morpha made up the least numbers with 1 species (0.38%). 167 species identified in our research materials were found to be close to 124 species according to Khamraev’s data in 2003, (KJ: 0.25), as well, 146 species according to Ganjaeva’s data in 2021 (KJ: 0.30). According to the distribution of hemipterans in the Southern Aral Sea Region in landscapes, 89 species (34.5%) were identified in agro-biocenoses, 85 species (32.9%) in the Lower Amudarya Biosphere Reserve, 83 species (32.29%) in Kyzylkum desert areas, 19 species (7.36%) on water and water banks, as well, 100 species (38.7%) in Ustyurt. Based on the density and number of 167 species of hemipterans distributed in the natural and anthropogenic regions of the Southern Aral Sea, 13 species were recorded as very rare (7.8%), 25 species-rare (15%), 63 species-permanent (38%), 27 species-common (16.1%), and 39 species-very common (23.3%).